Multiple Myeloma (Part 2) - Update on The Approach to Bone Disease - Guedes, Alex; Becker, Ricardo Gehrke; Teixeira, Luiz Eduardo Moreira (Revista Brasileira de Ortopedia, 2023)
The increase in life expectancy of the world population has led to a concomitant increase in the prevalence of multiple myeloma (MM), a disease that usually affects the elderly population. Bone lesions are frequent in patients with this condition, demanding an early approach, from drug treatment, through radiotherapy to orthopedic surgery (prophylactic or therapeutic) with the objective of preventing or delaying the occurrence of fracture, or, when this event has already occurred, treat it through stabilization or replacement (lesions located in the appendicular skeleton) and/or promote stabilization and spinal cord decompression (lesions located in the axial skeleton), providing rapid pain relief, return to ambulation and resocialization, returning quality of life to patients. The aim of this review is to update the reader on the findings of pathophysiology, clinical, laboratory and imaging, differential diagnosis and therapeutic approach of multiple myeloma bone disease (MMBD).
Keywords: Diphosphonates; Fractures Spontaneous; Multiple myeloma; Prophylactic Surgical procedures; Orthopedic procedures; Radiotherapy.